2013
DOI: 10.1103/physrevb.87.094116
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stress-strain behavior and stress-induced phase transitions in soft Pb(Zr1xTix)O

Abstract: Temperature-dependent stress-strain behavior of various soft PZT (Pb 0.98 Ba 0.01 (Zr 1-x Ti x ) 0.98 Nb 0.02 O 3 , 0.40 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 56 publications
6
26
1
Order By: Relevance
“…19,20 The mechanically induced decrease in polarisation closely corresponds to the observed remanent polarisation during electrical loading. In addition, previous investigations on the mechanical properties of PZT 55-45 have shown the remanent strain of unpoled samples after mechanical compression to be 0.30%, 19,20 which when combined with the electrically induced remanent strain (0.35%) during poling ( Fig. 1(b)) shows excellent agreement with the observed remanent strain during mechanical loading of poled samples (0.64%).…”
Section: A Materials Preparation and Macroscopic Propertiessupporting
confidence: 58%
See 1 more Smart Citation
“…19,20 The mechanically induced decrease in polarisation closely corresponds to the observed remanent polarisation during electrical loading. In addition, previous investigations on the mechanical properties of PZT 55-45 have shown the remanent strain of unpoled samples after mechanical compression to be 0.30%, 19,20 which when combined with the electrically induced remanent strain (0.35%) during poling ( Fig. 1(b)) shows excellent agreement with the observed remanent strain during mechanical loading of poled samples (0.64%).…”
Section: A Materials Preparation and Macroscopic Propertiessupporting
confidence: 58%
“…9 From the difference in position between (111) and ( 111) peaks, domain switching can be estimated to generate a maximum strain of approximately 0.7% along h111i directions. Previous laboratory diffraction measurements on the same material 19,20 reported a slight distortion of the diffraction profile attributed to the presence of a minority tetragonal phase. This distortion has not been observed here.…”
Section: Resultsmentioning
confidence: 80%
“…The order of magnitude of the Young's modulus seems reasonable and consistent with published data. 25,26 Following the same principle, apparent local material parameters can be identified. To be rigorously performed, however, this approach would need an appropriate micromechanical approach in order to define the electric field and stress in a given crystallographic orientation.…”
Section: Discussion On the Interpretation Of The Blocking Force Tmentioning
confidence: 99%
“…Such a phase transformation has been observed for the material of this study under the application of high compressive stress. 26 Fig. 19 shows the {200} and {111} peak profiles for w ¼ 0 under no applied electric field and for several levels of compressive stress.…”
Section: F Phase Changementioning
confidence: 99%
“…Previous characterization of the macroscopic electromechanical and stress--strain behavior has shown that uniaxial compressive stress can result in ferroelastic switching [22,23] as well as field--induced phase transitions in polycrystalline PZT. [24] Therefore, the primary aim of this work is to investigate role of stress on donor and acceptor--doped Pb(Zr,Ti)O3 through the characterization of the stress--and temperature--dependent direct piezoelectric response.…”
mentioning
confidence: 99%